Preparation method of three-dimensional silicon-carbon negative electrode material

By doping organic catalyst and template agent in silicon carbon materials to form carbon nanotubes, combining metal lithium deposition and phenolic resin structure, the problem of electronic conductivity difference of silicon carbon materials is solved, and its power and cycling performance is significantly improved, achieving More efficient electrochemical properties.

CN119170773APending Publication Date: 2024-12-20GUIZHOU HUIYANG TECH INNOVATION RES CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411343451.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The power and cycling performance of existing silicon-carbon materials are limited, mainly due to the difference in electronic conductivity and many defects of core nanosilicon and porous carbon, resulting in limited improvements in the first-time efficiency and power performance of the material.

Method used

By doping organic catalysts and template agents in organic phenolic compounds and aldehyde compounds, carbon nanotubes doped with spherical porous carbon, and depositing metal lithium on the carbon nanotubes to enhance the electron conductivity of porous carbon and combine with phenolic resin The structure reduces the expansion of silicon-carbon materials, and finally mixes and coats it with liquid asphalt on the surface of the intermediate to improve power performance.

Benefits of technology

It significantly improves the first efficiency, power performance and cycling performance of silicon carbon materials, reduces the expansion of the material, improves the specific capacity and conductivity, and improves the conductivity during the charging and discharging process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170773A_ABST
    Figure CN119170773A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a three-dimensional silicon-carbon negative electrode material, which comprises the following steps: adding an organic phenol compound, a catalyst and an organic template into an alkaline solution, uniformly mixing, adding an aldehyde compound, uniformly mixing, carrying out condensation polymerization, filtering, activating, and introducing carbonization gas to obtain carbon nanotube doped spherical porous carbon; transferring the carbon nanotube doped spherical porous carbon into a tubular furnace, and introducing lithium hydride gas for metal lithium deposition to obtain lithium / carbon nanotube doped porous carbon; the preparation method comprises the following steps: depositing and passivating nano silicon by a silane cracking method to obtain an intermediate, uniformly mixing the intermediate with liquid asphalt, and carbonizing to obtain the modified asphalt. The power performance, the cycle performance and the first efficiency of the silicon-carbon material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery material preparation, and specifically is a method for preparing a three-dimensional silicon-carbon negative electrode material. Background Art

[0002] Silicon-carbon materials are composed of porous carbon and nano-silicon deposited in the pores thereof, and rely on the porous structure of the porous carbon itself and the high specific capacity of its nano-silicon to reduce expansion, improve cycle performance and improve the specific capacity of silicon-carbon materials. However, due to the large number of defects in porous carbon itself, the initial efficiency of the material is reduced and its power performance is reduced. Although some researchers have improved the electronic conductivity of the material by doping non-metals or metals in porous carbon, or coating the surface with materials with high electronic or ionic conductivity, the electronic or ionic conductivity of the material during charging and discharging is improved to improve the rate performance. For example, patent application number CN202210396110.9 discloses a fast ion conductor-coated silicon-carbon composite material and a preparation method thereof. The composite material has a core-shell structure, with Si-SiO X The composite body has a silicon-based material as the core, an outer shell of 10-40% by mass of fast ion conductor, 1-10% of conductive agent, 1-10% of metal oxide, and the rest is amorphous carbon. Although the initial efficiency of the material and its power performance are improved, the electronic and ionic conductivity of the material core has not been improved, resulting in limited improvement in the power performance of the material. Patent publication number CN 116137324A discloses a metal-doped amorphous carbon-coated silicon-carbon composite material, a preparation method and its application. The composite material is composed of nano-silicon and porous carbon as the core, and a shell of rare earth metal-doped amorphous carbon. However, due to the poor electronic conductivity of the nano-silicon and porous carbon in the core and their many defects, its power performance deviates. Summary of the invention

[0003] The purpose of the present invention is to overcome the above-mentioned problems and provide a method for preparing a three-dimensional silicon-carbon negative electrode material that can improve the power performance, cycle performance and initial efficiency of the silicon-carbon material.

[0004] A method for preparing a three-dimensional silicon-carbon negative electrode material of the present invention comprises the following steps:

[0005] Step S1: adding the organic phenol compound, the organic catalyst and the organic amine template to an organic alkaline solution to prepare a 5-20wt% solution according to the mass ratio of organic phenol compound: organic catalyst: organic amine template: aldehyde compound = 100: 1-5: 5-20: 100-200, adding the aldehyde compound and mixing evenly, carrying out polycondensation reaction at a temperature of 150-250° C. for 6-24 hours, filtering, transferring the obtained filter residue to a tubular furnace and heating it to 900-1200° C., introducing water vapor for activation for 6-24 hours, cooling it to 700-1000° C., changing to a carbon source gas, introducing it at a flow rate of 50-200 SCCM for 60-300 minutes, and obtaining carbon nanotube-doped spherical porous carbon;

[0006] Step S2: transferring the carbon nanotube-doped spherical porous carbon to a tube furnace, exhausting the air in the tube, heating to 850-1000° C., introducing lithium hydride gas, and performing metal lithium deposition at a flow rate of 100-500 SCCM for 30-300 min to obtain lithium / carbon nanotube-doped porous carbon;

[0007] Step S3: transfer the lithium / carbon nanotube-doped porous carbon to a fluidized bed, heat to 450-550° C., introduce a silane mixed gas (volume ratio of silane gas: nitrogen = 1-5:10), deposit at a flow rate of 100-500 ml / min for 60-600 min, cool to 300-500° C., introduce an oxygen mixed gas (volume ratio of oxygen: acetylene = 10:1-5), passivate at a gas flow rate of 100-500 ml / min for 60-600 min, and obtain an intermediate;

[0008] According to the mass ratio of intermediate: liquid asphalt = 100: 5-10, the intermediate and liquid asphalt are evenly mixed, and carbonized at a temperature of 600-900° C. for 1-6 hours to obtain a three-dimensional silicon-carbon negative electrode material.

[0009] The above-mentioned method for preparing a three-dimensional silicon-carbon negative electrode material, wherein: the organic phenol compound described in step S1 is one of 2,4-dimethylphenol, resorcinol, hydroquinone, 1,3,5-benzenetriol or phenol; the aldehyde compound is one of cinnamaldehyde, acrolein, acrolein, n-valeraldehyde, m-hydroxybenzaldehyde or 3-hydroxybenzaldehyde; the organic amine template is one of tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetraethylammonium bromide, tetrapropylammonium chloride or tetrabutylammonium chloride; the alkaline solution is one of dimethylamine, ethylenediamine, triethylamine, diethylamine, n-propylamine or triethanolamine; the organic catalyst is one of tributylphosphine, triphenylphosphine, pentafluorophenylphosphine or tributylphosphine.

[0010] The above-mentioned method for preparing a three-dimensional silicon-carbon negative electrode material, wherein: the silane gas described in step S2 is one of monosilane, disilane, dichlorosilane or trichlorosilane. Compared with the existing technology, the present invention has obvious beneficial effects. It can be seen from the above technical scheme: the present invention generates carbon nanotubes in a carbon source gas atmosphere by doping organic catalysts and organic templates in organic phenol compounds and aldehyde compounds, using the porous structure formed by carbonization of the organic template, and the organic catalyst, thereby restraining the expansion of nano-silicon during the charge and discharge process, and interacting with the generated phenolic resin porous structure to reduce the expansion of silicon-carbon materials. Metal lithium is deposited on spherical porous carbon doped with carbon nanotubes to improve the electronic conductivity of porous carbon and reduce its defects, thereby improving the initial efficiency and improving the power performance. The present invention adopts mixing and coating with asphalt on the surface of the intermediate to reduce expansion and increase power. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 This is the SEM image of the three-dimensional silicon-carbon negative electrode material prepared in Example 1. DETAILED DESCRIPTION

[0012] Embodiment 1:

[0013] A method for preparing a three-dimensional silicon-carbon negative electrode material comprises the following steps:

[0014] Step S1: 100 g of 2,4-dimethylphenol, 3 g of tributylphosphine, and 10 g of tetrapropylammonium hydroxide are added to 1130 g of dimethylamine solution to prepare a solution with a mass concentration of 10 wt%, 150 g of cinnamaldehyde is added and mixed evenly, and a polycondensation reaction is carried out at a temperature of 200° C. for 12 h, filtered, and the obtained filter residue material is transferred to a tubular furnace and heated to 1000° C. and water vapor is introduced for activation for 12 h, then cooled to 850° C., ethylene gas is introduced and introduced at a flow rate of 100 SCCM for 150 min to obtain carbon nanotube-doped spherical porous carbon;

[0015] Step S2: transferring the carbon nanotube-doped spherical porous carbon to a tube furnace, exhausting the air in the tube, heating to 950° C., introducing lithium hydride gas, and performing metallic lithium deposition at a flow rate of 300 SCCM for 150 min to obtain lithium / carbon nanotube-doped porous carbon;

[0016] Step S3: Transfer the lithium / carbon nanotube-doped porous carbon to a fluidized bed, heat it to 500°C, introduce a silane mixed gas (volume ratio, silane: nitrogen = 3:10), deposit it at a flow rate of 300 ml / min for 300 min, cool it to 400°C, introduce an oxygen mixed gas (volume ratio, oxygen: acetylene = 10:3), passivate it at a gas flow rate of 300 ml / min for 300 min, and obtain an intermediate; mix 100 g of the intermediate with 8 g of liquid asphalt, heat it to 750°C under a nitrogen atmosphere and carbonize it for 3 h, and cool it down to room temperature under a nitrogen atmosphere to obtain a three-dimensional silicon-carbon negative electrode material.

[0017] Embodiment 2:

[0018] A method for preparing a three-dimensional silicon-carbon negative electrode material comprises the following steps:

[0019] Step S1: 100 g of resorcinol, 1 g of triphenylphosphine, and 5 g of tetrabutylammonium hydroxide are added to 2120 g of ethylenediamine solution to prepare a solution with a mass concentration of 5 wt%, 100 g of acrolein is added and mixed evenly, and a polycondensation reaction is carried out at a temperature of 150° C. for 24 h, filtered, and the obtained filter residue material is transferred to a tubular furnace and heated to 900° C. and water vapor is introduced for activation for 24 h, then cooled to 700° C., and methane gas is introduced at a flow rate of 50 SCCM for 300 min to obtain carbon nanotube-doped spherical porous carbon;

[0020] Step S2: transferring the carbon nanotube-doped spherical porous carbon to a tube furnace, introducing nitrogen to exhaust the air in the tube, heating to 850° C., introducing lithium hydride gas, and performing metallic lithium deposition at a flow rate of 100 SCCM for 300 min to obtain lithium / carbon nanotube-doped porous carbon;

[0021] Step S3: Transfer the lithium / carbon nanotube-doped porous carbon to a fluidized bed, heat it to 450°C, introduce a disilane mixed gas (volume ratio, disilane: nitrogen = 1:10), deposit it at a flow rate of 500 ml / min for 60 minutes, cool it to 300°C, introduce an oxygen mixed gas (volume ratio, oxygen: acetylene = 10:1), passivate it at a gas flow rate of 100 ml / min for 600 minutes, and obtain an intermediate; mix 100g of the intermediate with 5g of liquid asphalt, raise the temperature to 600°C in a nitrogen atmosphere, and carbonize it for 6 hours to obtain a three-dimensional silicon-carbon negative electrode material.

[0022] Embodiment 3:

[0023] A method for preparing a three-dimensional silicon-carbon negative electrode material comprises the following steps:

[0024] Step S1: 100 g of hydroquinone, 5 g of pentafluorophenylphosphine, and 20 g of tetraethylammonium hydroxide are added to 625 g of triethylamine solution to prepare a solution with a mass concentration of 20 wt%, 200 g of acrolein is added and mixed evenly, and a polycondensation reaction is carried out at a temperature of 250° C. for 6 h, filtered, and the obtained filter residue material is transferred to a tubular furnace and heated to 1200° C. and water vapor is introduced for activation for 6 h, then cooled to 1000° C., acetylene gas is introduced at a flow rate of 200 SCCM for 60 min, and carbon nanotube-doped spherical porous carbon is obtained;

[0025] Step S2: transferring the carbon nanotube-doped spherical porous carbon to a tube furnace, exhausting the air in the tube, heating to 1000° C., introducing lithium hydride gas, and depositing metallic lithium at a flow rate of 500 SCCM for 30 min to obtain lithium / carbon nanotube-doped porous carbon;

[0026] Step S3: Transfer the lithium / carbon nanotube-doped porous carbon to a fluidized bed, heat it to 550°C, introduce a dichlorosilane mixed gas (volume ratio, dichlorosilane: nitrogen = 5:10), deposit it at a flow rate of 500 ml / min for 60 minutes, cool it to 500°C, introduce an oxygen mixed gas (volume ratio, oxygen: acetylene = 10:5), passivate it at a gas flow rate of 500 ml / min for 60 minutes, and obtain an intermediate; mix 100g of the intermediate with 10g of liquid asphalt, heat it to 900°C in a nitrogen atmosphere and carbonize it for 1 hour to obtain a three-dimensional silicon-carbon negative electrode material.

[0027] Comparative Example 1:

[0028] A method for preparing a silicon-carbon negative electrode material comprises: the difference from Example 1 is that tributylphosphine and tetrapropylammonium hydroxide are not added in step S1, and the rest is the same as Example 1.

[0029] Comparative Example 2:

[0030] A method for preparing a silicon-carbon negative electrode material comprises: the difference from Example 1 is that lithium hydride gas is not introduced in step S2, and the rest is the same as Example 1.

[0031] Comparative Example 3:

[0032] The difference from Example 1 is that no asphalt coating is performed, that is, the intermediate in step S3 is used as the negative electrode material, and the rest is the same as Example 1.

[0033] Test example:

[0034] 1. Scanning electron microscope (SEM) test

[0035] The silicon-carbon composite material in Example 1 was subjected to SEM testing, and the test results are as follows: Figure 1 As shown. Figure 1It can be seen that the material presents a three-dimensional granular structure, and the particle size is between 5-10 μm.

[0036] 2. Physical and chemical tests and button cell battery tests

[0037] Refer to GB / T38823-2020 "Silicon Carbon" to test the specific surface area and tap density of the silicon-carbon composite material, use a four-probe tester to test the powder conductivity of the silicon-carbon composite material, and test the gas production of the powder material (add m1 g of powder material to deionized water at 45°C and soak it for 48 hours to test its gas production V1, and calculate the gas production of the powder material = V1 / m1*100%); and soak the material in deionized water to test the residual alkali of the material.

[0038] The silicon-carbon composite materials in Examples 1-3 and Comparative Examples 1-3 were used as negative electrode materials for lithium-ion batteries to prepare button batteries, and the preparation method was as follows:

[0039] Add binder, conductive agent and solvent to the composite material, stir to make slurry, coat on copper foil, dry and roll to obtain negative electrode sheet; the binder used is polyvinylidene fluoride (PVDF), the conductive agent is conductive carbon black (SP), the solvent is N-methylpyrrolidone (NMP), the amount ratio of composite material, SP, PVDF and NMP is 90g:4g:6g:250mL; the electrolyte is lithium hexafluorophosphate (LiPF6), the mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1 is used as solvent, and the electrolyte concentration is 1mol / L; the metal lithium sheet is the counter electrode, and the diaphragm is a polypropylene (PP) film. The button cell is assembled in an argon-filled glove box.

[0040] The electrochemical performance of button cells comprising the silicon-carbon composite materials of Examples 1-3 and Comparative Examples 1-3 was tested using a Wuhan Blue Power CT2001A battery tester with a charge and discharge voltage range of 0.005 V to 2.0 V and a charge and discharge rate of 0.1 C. The rate performance of the material was also tested (1C / 0.1C).

[0041] The thickness D1 of the negative electrode sheet of the button cell containing the silicon-carbon composite materials of Examples 1-3 and Comparative Examples 1-3 after rolling was tested, and then the full-charge thickness D2 of the negative electrode sheet of the button cell fully charged to 100% SOC was dissected, and then the expansion rate was calculated:

[0042] The expansion ratio is = (D1-D2) / D1*100%. The test results are shown in Table 1.

[0043] Table 1

[0044]

[0045] It can be seen from the data in Table 1 that the specific capacity, first efficiency, powder conductivity, full charge expansion and DCR of the silicon-carbon composite material prepared by the present invention are significantly better than those of the comparative example. The reason is that the spherical porous carbon doped with carbon nanotubes reduces the powder resistance and the expansion of silicon during the bound charge and discharge process, thereby improving the rate performance; at the same time, the doping of metallic lithium reduces its irreversible capacity loss and improves the first efficiency; and the doping of organic templates increases the pore volume, increases the amount of silicon deposited during the deposition process, and improves the specific capacity.

[0046] 3. Soft pack battery test

[0047] The silicon-carbon composite materials of Examples 1-3 and Comparative Examples 1-3 were mixed with 95% artificial graphite as negative electrode materials to prepare negative electrode sheets. 1 / 3 Co 1 / 3 Mn 1 / 3 O2) as the positive electrode; lithium hexafluorophosphate (LiPF6) as the electrolyte, a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (DEC) in a volume ratio of 1:1 as the solvent, and an electrolyte concentration of 1.3 mol / L; Celgard 2400 membrane as the separator, and a 5Ah soft pack battery was prepared. The liquid absorption capacity, rate and rate performance of the negative electrode were tested respectively.

[0048] a. Liquid absorption capacity test

[0049] Use a 1mL burette and draw 1mL of electrolyte, add a drop on the surface of the electrode, and time until the electrolyte is completely absorbed, and record the time t. The test results are shown in Table 2. The test results are shown in Table 2.

[0050] b. Rate and cycle performance test

[0051] The soft-pack batteries including the composite materials of Examples 1-3 and Comparative Examples 1-2 were subjected to cycle performance tests and rate tests.

[0052] Rate test: Test the constant current ratio of the material under 2C conditions, constant current ratio = 2C constant current capacity / (2C constant current capacity + 0.1C constant voltage capacity).

[0053] Cycle performance: test voltage range 2.5-3.65V, 1C / 1C, temperature 25±3℃, 500 cycles. The test results are shown in Table 2.

[0054] Table 2

[0055]

[0056]

[0057] It can be seen from Table 2 that the liquid absorption capacity, cycle performance and constant current ratio of the soft-pack lithium-ion battery prepared using the silicon-carbon composite material of the present invention are better than those of the comparative example. The reason is that the silicon-carbon composite material of the present invention has a high specific surface area and a low powder resistivity, which improves the liquid retention performance of the battery. At the same time, the embodiment material has low expansion, thereby improving the cycle performance and constant current ratio.

[0058] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a three-dimensional silicon-carbon negative electrode material, comprising the following steps: Step S1: adding the organic phenol compound, the organic catalyst, and the organic amine template to an organic alkaline solution to prepare a 5-20wt% solution according to the mass ratio of organic phenol compound: organic catalyst: organic amine template: aldehyde compound = 100: 1-5: 5-20: 100-200, adding the aldehyde compound and mixing evenly, carrying out polycondensation reaction at a temperature of 150-250° C. for 6-24 hours, filtering, transferring the obtained filter residue material to a tubular furnace and heating it to 900-1200° C., introducing water vapor for activation for 6-24 hours, cooling it to 700-1000° C., changing to a carbon source gas, introducing it at a flow rate of 50-200 SCCM for 60-300 minutes, and obtaining carbon nanotube-doped spherical porous carbon; Step S2: The carbon nanotube-doped spherical porous carbon is transferred to a tube furnace, the air in the tube is exhausted, heated to 850-1000 ° C, lithium hydride gas is introduced, and metallic lithium is deposited at a flow rate of 100-500 SCCM for 30-300 min to obtain lithium / carbon nanotube-doped porous carbon; Step S3: transferring the lithium / carbon nanotube-doped porous carbon to a fluidized bed, heating to 450-550° C., introducing a silane mixed gas with a volume ratio of silane gas: nitrogen = 1-5:10, depositing at a flow rate of 100-500 ml / min for 60-600 min, cooling to 300-500° C., introducing an oxygen mixed gas with a volume ratio of oxygen: acetylene = 10:1-5, passivating at a gas flow rate of 100-500 ml / min for 60-600 min, and obtaining an intermediate; According to the mass ratio of intermediate: liquid asphalt = 100: 5-10, the intermediate and liquid asphalt are evenly mixed, and carbonized at a temperature of 600-900°C for 1-6h to obtain a three-dimensional silicon-carbon negative electrode material.

2. A method for preparing a three-dimensional silicon-carbon negative electrode material according to claim 1, wherein the organic phenol compound described in step S1 is one of 2,4-dimethylphenol, resorcinol, hydroquinone, 1,3,5-benzenetriol or phenol; the aldehyde compound is one of cinnamaldehyde, acrolein, acrolein, n-valeraldehyde, m-hydroxybenzaldehyde or 3-hydroxybenzaldehyde; the organic amine template is one of tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetraethylammonium bromide, tetrapropylammonium chloride or tetrabutylammonium chloride; the alkaline solution is one of dimethylamine, ethylenediamine, triethylamine, diethylamine, n-propylamine or triethanolamine; the organic catalyst is one of tributylphosphine, triphenylphosphine, pentafluorophenylphosphine or tributylphosphine.

3. The method for preparing a three-dimensional silicon-carbon negative electrode material according to claim 1, wherein the silane gas in step S2 is one of monosilane, disilane, dichlorosilane or trichlorosilane.

Citation Information

Cited By

  • Preparation method and application of phenolic resin-based spherical porous carbon negative electrode material

    CN121800175A